Environmental, social, and governance (ESG) performance and firm perfomance: Does sharia compliance matters? - Yandi Suprapto; Derrick Sebastian; Isnaini Nuzula Agustin (Universitas Nusa Cendana, 2026)
This study aims to examine the influence of Environmental, Social, and Governance (ESG) Performance on Firm Performance and the moderating role of Shariah Compliance in companies in Indonesia. The study uses a quantitative approach with an explanatory research design and utilizes panel data of 305 company observations during the 2019–2024 period. The analysis was conducted using a regression model with Return on Equity (ROE) and Tobin’s Q as proxies for Firm Performance, and Shariah Compliance as a moderating variable. The results show that ESG Performance has a positive and significant effect on ROE, but does not significantly affect Tobin’s Q. At the same time, Shariah Compliance has a direct negative effect on firm performance, but is proven to strengthen the relationship between ESG Performance and Firm Performance. These findings indicate that ESG implementation supported by compliance with sharia principles can improve company performance more optimally, both in terms of profitability and firm value. Therefore, companies need to integrate ESG practices with sharia principles as a strategy to improve long-term performance, strengthen corporate legitimacy, and increase investor confidence. Keywords: ESG Performance; Firm Performance; Sharia Compliance; ROE; Tobin’s Q